2019
DOI: 10.1016/j.pedneo.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Parental concern of feeding difficulty predicts poor growth status in their child

Abstract: Background: Parents often express concerns about feeding difficulties in their child. We hypothesized that these parental concerns were associated with adverse growth status in early childhood. We aimed to determine the prevalence of such concerns and whether these concerns were associated with adverse growth status in early childhood. Methods: We performed a cross-sectional study among healthy children aged 12e36 months attending three well-baby clinics in three urban areas in Malaysia and Singapore between D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
2
7
1
Order By: Relevance
“…Of the 54 studies included in the synthesis, four utilized an RCT design (da Costa et al, 2017; Mallan et al, 2016; Sanchez et al, 2018; Tauman et al, 2017) and eight were reviews (Dunn & Lessen, 2017; Gibson & Cooke, 2017; Nicklaus, 2016; Taylor & Emmett, 2019; Verhage et al, 2018; Walton et al, 2017; Watson et al, 2018; Wolstenholme et al, 2020). All other included studies were of observational design (19 cohort studies: Harris et al, 2016; Maslin et al, 2016; Monnery‐Patris et al, 2015; Smith et al, 2017; Specht et al, 2018; Amarger et al, 2015; Cardona Cano et al, 2015; Cole et al, 2018; Cole, Wang, et al, 2017; de Barse et al, 2017; de Barse et al, 2016; Emmett et al, 2018; Fildes et al, 2016; Hollis et al, 2016; Johnson et al, 2016; Oliveira et al, 2015; Pang et al, 2020; Reis et al, 2015; Tharner et al, 2015; 16 cross‐sectional studies: Bell et al, 2018; Coulthard & Sahota, 2016; Finnane et al, 2017; Fu et al, 2018; Helland et al, 2017; Holley et al, 2020; Kaar et al, 2016; Marlina et al, 2020; Maslin et al, 2015; Nederkoorn et al, 2015; Podlesak et al, 2017; Rahill et al, 2019; Ramos et al, 2017; Sandvik et al, 2018; van der Horst et al, 2016; Lee et al, 2019; five longitudinal studies: Bilgin & Wolke, 2017; Boots et al, 2019; Costantini et al, 2019; Micali et al, 2016; Steinsbekk et al, 2017; one correlational study: Griffith et al, 2018,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 54 studies included in the synthesis, four utilized an RCT design (da Costa et al, 2017; Mallan et al, 2016; Sanchez et al, 2018; Tauman et al, 2017) and eight were reviews (Dunn & Lessen, 2017; Gibson & Cooke, 2017; Nicklaus, 2016; Taylor & Emmett, 2019; Verhage et al, 2018; Walton et al, 2017; Watson et al, 2018; Wolstenholme et al, 2020). All other included studies were of observational design (19 cohort studies: Harris et al, 2016; Maslin et al, 2016; Monnery‐Patris et al, 2015; Smith et al, 2017; Specht et al, 2018; Amarger et al, 2015; Cardona Cano et al, 2015; Cole et al, 2018; Cole, Wang, et al, 2017; de Barse et al, 2017; de Barse et al, 2016; Emmett et al, 2018; Fildes et al, 2016; Hollis et al, 2016; Johnson et al, 2016; Oliveira et al, 2015; Pang et al, 2020; Reis et al, 2015; Tharner et al, 2015; 16 cross‐sectional studies: Bell et al, 2018; Coulthard & Sahota, 2016; Finnane et al, 2017; Fu et al, 2018; Helland et al, 2017; Holley et al, 2020; Kaar et al, 2016; Marlina et al, 2020; Maslin et al, 2015; Nederkoorn et al, 2015; Podlesak et al, 2017; Rahill et al, 2019; Ramos et al, 2017; Sandvik et al, 2018; van der Horst et al, 2016; Lee et al, 2019; five longitudinal studies: Bilgin & Wolke, 2017; Boots et al, 2019; Costantini et al, 2019; Micali et al, 2016; Steinsbekk et al, 2017; one correlational study: Griffith et al, 2018,...…”
Section: Resultsmentioning
confidence: 99%
“…Five studies analysed sensory preferences (Coulthard & Sahota, 2016 ; Monnery‐Patris et al, 2015 ; Nederkoorn et al, 2015 ; Steinsbekk et al, 2017 ; Tauman et al, 2017 ), four on effects of prematurity (Bilgin & Wolke, 2017 ; Griffith et al, 2018 ; Johnson et al, 2016 ; Sanchez et al, 2018 ) and two on effects of cow's milk exclusion (Maslin et al, 2015 ; Maslin et al, 2016 ). The remaining studies focused on a combination of these factors (Cardona Cano et al, 2015 ; Cole et al, 2018 ; da Costa et al, 2017 ; Gibson & Cooke, 2017 ; Helland et al, 2017 ; Hollis et al, 2016 ; Lee et al, 2019 ; Marlina et al, 2020 ; Nicklaus, 2016 ; Oliveira et al, 2015 ; Rahill et al, 2019 ; Ramos et al, 2017 ; Reis et al, 2015 ; Sandvik et al, 2018 ; Smith et al, 2017 ; Tharner et al, 2015 ; van der Horst et al, 2016 ; Verhage et al, 2018 ; Werthmann et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not analyse whether having just one or both factors affected the child's height status as number of children reported to have both factors were small. A study of healthy children (12–36 months) by Lee et al showed that children who had food refusal were more likely to have growth faltering, while children with limited variety of food intake were less likely to have short stature ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…They thus may be less concerned about child overweight than mothers in other countries. Moreover, monitoring or restricting unhealthy food intake may be associated with maternal concern about pediatric health problems, resulting in a decreased/lack of appetite or chronic diseases, such as obesity [49,55,56].…”
Section: Discussionmentioning
confidence: 99%